The comparative analysis of the specifications of weekly training cycles as compared to the training stages of a long jumper - Dulgheru, M. (Science, Movement & Health, 2013)
The Training Objectives for a long jumper are represented, on the one hand, by the activities of learning and perfecting the techniques of the jump and, on the other hand, by activities meant to develop the motric capacity. The effort characteristic to long jumps is an intense one; it takes time and requires constant improvement of the motric capacities, and is essential for attaining the high performances. The Present research intends to validate the hypothesis thus formulated: if we plan the training that aims at the preparation stages, that precedes the competition, as well as those occurring during and after competitions or the recuperation, for the long jump competition, then we have to take into consideration the technical and method particularities in order to choose the right means and dosage of effort during the training that has to be different between the weekly training cycles. These aspects are essential between the weekly training cycles for each stage. The present research aims at the Olympic cycle, of 4 years, period in which we registered all the training means used during each stage, taking into consideration the volume of training as well as the intensity of the effort. The Methods used for the research in the scientific endeavour of this research were the following: the bibliographic method, the making of a record, the analysis and the comparison of data, as well as the statistical method. The research has at its basis the documents according to which the activity of a long jumper was planned (the author of the research) who had high results in the world classifications of this competition (7.14 m). The General Discution and Conclusion of the present research underlines the fact that the training weekly cycles differ according to the preparatory stages, as to the diversity of the used means during the training course as well as from the point of view of the training effort whose indicators are different, in accordance to the demands and objectives of that particular stage. Domain experts have demonstrated the effort means and indicators whose parameters are differentiated according to the requirements and objectives of each stage and presents structures, periodizations and training cycles as well as action technologies in applying the weekly cycles whose principles can be perfectly applied to the conclusions of the paper herewith.